A Cross-Country Experiment into the Labelling Effects of Meat-Alternatives - Veltmeijer, Johannes Hendrik (2022)
Purpose – The purpose of this research is to evaluate the influence of different product labels on meat-alternatives across two countries. In doing so, the research aims to identify geographical and cultural differences on the effectiveness of meat-alternatives’ labelling. Design/methodology – The research employed a survey experiment conducted in The Netherlands and in Brazil where participants were randomly assigned to one of 3 labels of meat alternative (“meatless” vs. “vegan” vs. “plant-based”) and were then asked their willingness-to-pay for the product in a hypothetical scenario. Findings – This study identified that there are differences between the two countries. The results of the survey have revealed that the meat-alternative label with the higher association with meat resulted in a higher willingness-to-pay in Brazil, while the ‘plant-based’ label resulted in the highest willingness-to-pay in The Netherlands. The study also identified that the use of the term ‘vegan’ can best be avoided when marketing a meat-alternative. Research limitations – The main limitations of this study are the sample, which is not representative for each entire country, as well as the hypothetical scenario. Originality – To the best of my knowledge, this is the first study that compares cross-country results on the effects of labeling on meat-alternatives in an emerging country and a developed European country.